The Protective Role of Carnosic Acid against Beta-Amyloid Toxicity in Rats - H. Rasoolijazi; N. Azad; M. T. Joghataei; M. Kerdari; F. Nikbakht; M. Soleimani (The Scientific World Journal)
Oxidative stress is one of the pathological mechanisms responsible for the beta- amyloid cascade associated with Alzheimer’s disease (AD). Previous studies have demonstrated the role of carnosic acid (CA), an effective antioxidant, in combating oxidative stress. A progressive cognitive decline is one of the hallmarks of AD. Thus, we attempted to determine whether the administration of CA protects against memory deficit caused by beta-amyloid toxicity in rats. Beta-amyloid (1–40) was injected by stereotaxic surgery into the Ca1 region of the hippocampus of rats in the Amyloid beta (Aβ) groups. CA was delivered intraperitoneally, before and after surgery in animals in the CA groups. Passive avoidance learning and spontaneous alternation behavior were evaluated using the shuttle box and the Y-maze, respectively. The degenerating hippocampal neurons were detected by fluoro-jade b staining. We observed that beta-amyloid (1–40) can induce neurodegeneration in the Ca1 region of the hippocampus by using fluoro-jade b staining. Also, the behavioral tests revealed that CA may recover the passive avoidance learning and spontaneous alternation behavior scores in the Aβ + CA group, in comparison with the Aβ group. We found that CA may ameliorate the spatial and learning memory deficits induced by the toxicity of beta-amyloid in the rat hippocampus.